A constructivist approach for teaching embedded systems - Ordinez, Leonardo Damian (2013)
Due to the technological breakthrough of recent years, electronic devices have become an important part of everyday life. Most of these devices falls within the class of systems called embedded systems. This article presents a proposal for a course on embedded systems. The proposal is based on aconstructivist approach to teaching, with particular emphasis on problem-based learning.